Gambaran Paparan Media Sosial Instagram, Pengetahuan, Sikap dan Perilaku Merokok pada Siswa MAN 2 Kota Tangerang Tahun 2024 - Nurfajriah, Indri; Aristi, Dela (Journal of Religion and Public Health, 2024)
Smoking is one of the public health problems. Data from the Indonesian Health Survey in 2023 showed that the prevalence of smokers aged 15-19 years was 56.5%, while according to BPS in 2023 smokers in Tangerang City were 14.79%. Exposure to negative information and content on Instagram can have both positive and negative effects on its users. The purpose of this study was to determine the description of exposure to Instagram social media, knowledge, attitudes and smoking behavior in adolescents at MAN 2 Tangerang City in 2024. This type of research is quantitative with a cross sectional design approach. Data analysis in the study used univariate tests. The sample in the study were MAN 2 Tangerang City students in grades X and XI of 157 respondents. The results showed that smoking behavior in students was 17.2%. The level of knowledge of respondents about the dangers of smoking is mostly good 54.8%. The majority of respondents' attitudes towards smoking behavior were positive 53.5%. Exposure to negative cigarette content on Instagram social media on students amounted to 81.5%. Students are exposed to educational content on the dangers of smoking on social mediaInstagram 93%. Therefore, schools are expected to provide guidance or education to all students regarding smoking behavior by utilizing Instagram social media. Educational content can be done by posting videos, posters, and pictures.Keywords: Adolescent, Instagram, Smoking behavior.